Aplikasi Informasi Posko Bencana Alam Berbasis Android - Setiawati, Irma Yunita; Handojo, Andreas; Purbowo, Anita Nathania (Jurnal Infra, 2015)
Within the last 10 years, there have been so many natural disasters such as tsunami, earthquakes, and the eruption of Mount Merapi in Yogyakarta. Many emergency shelters were built to accommodate the disasters survivors. It caused problems in processing information regarding existing aid. An application named